Systemic growth hormone deficiency causes mechanical and thermal hypersensitivity during early postnatal development. (June 2019) - Ford, Zachary K.; Dourson, Adam J.; Liu, Xiaohua; Lu, Peilin; Green, Kathryn J.; Hudgins, Renita C.; Jankowski, Michael P.
Highlights: Systemic GHD causes behavioral hypersensitivity at P7 and P14, but not P21. Primary afferent sensitization is observed in GHRHr KOs. Knockout of GHRHr changes DRG gene expression that is observed throughout development. Abstract: Injury during early postnatal life causes acute alterations in afferent function and DRG gene expression, which in addition to producing short-term sensitivity has the potential to influence nociceptive responses in adulthood. We recently discovered that growth hormone (GH) is a key regulator of afferent sensitization and pain-related behaviors during developmental inflammation of the skin. Peripheral injury caused a significant reduction in cutaneous GH levels, which corresponded with the observed hypersensitivity. However, it has yet to be determined whether GH deficiency (GHD) is sufficient to drive peripheral sensitization in uninjured animals. Here, we found that systemic GHD, induced by knockout of the GH release hormone receptor (GHRHr), was able to induce behavioral and afferent hypersensitivity to peripheral stimuli specifically during early developmental stages. GHD also produced an upregulation of many receptors and channels linked to nociceptive processing in the DRGs at these early postnatal ages (P7 and P14). Surprisingly, P21 GHRHr knockouts also displayed significant alterations in DRG gene expression even though behavioral and afferent hypersensitivity resolved. These data support previous findings that GH is a key modulator of neonatal hypersensitivity. Results may provide insight into whether GH treatment may be a therapeutic strategy for pediatric pain.